DISSEMINATION OF THE HALAL VACCINATION OF COVID-19 IN EDUCATION OF THE RUMAH QUR'AN EL-FAJR FOUNDATION, PALEMBANG CITY - Bagus Setiawan; Ria Astina; Cindi Pramita (Sean Institute, 2023)
Vaccination is an alternative to increase a person's immune system, vaccination is a liquid given to prevent the spread of the covid-19 virus. This virus can only attack humans and enter the body through the respiratory tract (spread through the air). This virus is easily transmitted to people who have weeks of immune systems. The law uses permissible or permissible vaccinations related to the explanation of the MUI (Indonesian Ulama Council) in order to prevent and reduce cases of the covid-19 virus in Indonesia